Multifunctional PCz/BaO nanocomposites: Ionizing radiation shielding ability and enhanced electric conductivity - Beyazay, Emre; Karabul, Yasar; Korkut, Sibel Eken; Kilic, Mehmet; Ozdemir, Zeynep Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The present study deals with the production of multifunctional polymer-based nanocomposites having the ability of ionizing radiation shielding and enhanced electric conductivity. In this context, it is aimed to obtain a new environmentally-friendly lead-free material with both high electric conductivity and ionizing radiation shielding features by reinforcing polycarbazole (PCz), a conductive polymer with BaO nanoparticles having a high effective atomic number. PCz matrix and BaO nanoparticles have been prepared by polymerization and coprecipitation methods, respectively. The surface morphology of the PCz matrix and nano BaO particles have been characterized by SEM and TEM images. Additionally, the optical band gaps of the samples have been calculated by using UV-visible spectroscopy. The lowest optical bandgap i.e. the highest electric conductivity has been observed for the 10 wt% BaO nanoparticle doped composite. On the other hand, the ionizing radiation shielding abilities of the samples have been evaluated in the context of mass attenuation coefficient, half-value layer, mean free path, effective atomic number, and effective electron density determined both experimentally and theoretically. Experimental measurements have been carried out by using NaI(Tl) detector and point radioactive sources (Ba-133, Cs-137, and Co-60) in the narrow beam geometry. The theoretical calculations have been performed by WinXCom software. A reasonable agreement between the experimental and WinXCom results has been found. Consequently, it has been determined that the maximum radiation shielding ability has been detected against 81 keV radiation for the PCz/30 wt% BaO nanocomposite. The composite has also a lower bandgap than pristine PCz. In this respect, the PCz/30 wt% BaO nanocomposite can have a promising potential in both medical and electronic applications that require high electric conductivity and ionizing radiation shielding ability.
Keywords: Conducting polymers; Nanocomposites; Radiation shielding; WinXCom; UV -Visible spectrum; COMPOSITES; ATTENUATION; Nuclear Science & Technology